SAFETY OF TRANSPORTATION OF OVERSIZED AND EXCESSIVE LOADS (Perner's Contacts, 2016)
The paper is dealing with the issues of safety in planning and realization of oversized and excessive goods transportation. It points to the growing importance of these transportations for the economy of the state. Further it points to selected risks that could cause the emergency event during this transportation and possibilities of their elimination, which may lead to the increased safety of transportation of oversized and excessive loads.
Keywords: safety; transport; oversized; excessive; protection; special